Memory, Autofiction, and Identity in Video Games: The Case of Looking Back. An Interview with Kristopher Poulin-Thibault - Poirier-Poulin, Samuel (Loading)

(untitled) (Canadian Game Studies Association, 2020)
Indie developer Kristopher Poulin-Thibault speaks with Samuel Poirier-Poulin (no relation) about the creation of the video game Looking Back. The interview starts with a brief discussion about the RPG genre and quickly moves toward a broader discussion about autofiction, trauma, time, memory, retro games, and language. Poulin-Thibault reflects on the interconnectedness of these topics and their influence on identity construction.